Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.pgen.1004200
|View full text |Cite
|
Sign up to set email alerts
|

Lsd1 Restricts the Number of Germline Stem Cells by Regulating Multiple Targets in Escort Cells

Abstract: Specialized microenvironments called niches regulate tissue homeostasis by controlling the balance between stem cell self-renewal and the differentiation of stem cell daughters. However the mechanisms that govern the formation, size and signaling of in vivo niches remain poorly understood. Loss of the highly conserved histone demethylase Lsd1 in Drosophila escort cells results in increased BMP signaling outside the cap cell niche and an expanded germline stem cell (GSC) phenotype. Here we present evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 59 publications
4
74
0
Order By: Relevance
“…5D,H) despite producing a very strong germline differentiation defect. It is possible that our lsd1 RNAi experiment, which allowed some egg chamber budding, produced lower Lsd1 inhibition than in previous analyses using the same RNAi approach and lsd1 null mutations (Eliazer et al, 2014). The set of phenotypes that we observed allow us to deduce that reduction of Lsd1 can produce germline differentiation defects in the absence of an apparent transformation of ECs towards cap cell identity, as observed for loss of Smo and Yki function.…”
Section: Interactions Among Lsd1 Hh and Ykimentioning
confidence: 63%
See 3 more Smart Citations
“…5D,H) despite producing a very strong germline differentiation defect. It is possible that our lsd1 RNAi experiment, which allowed some egg chamber budding, produced lower Lsd1 inhibition than in previous analyses using the same RNAi approach and lsd1 null mutations (Eliazer et al, 2014). The set of phenotypes that we observed allow us to deduce that reduction of Lsd1 can produce germline differentiation defects in the absence of an apparent transformation of ECs towards cap cell identity, as observed for loss of Smo and Yki function.…”
Section: Interactions Among Lsd1 Hh and Ykimentioning
confidence: 63%
“…The Lsd1 phenotype was previously shown to be partially suppressed by reducing the activity of En or Hh, which is normally induced by En in cap cells, and was partially phenocopied by ectopic En expression but not by ectopic Hh (Eliazer et al, 2014). That study suggested that En induction might be one of several crucial effectors in ECs with reduced Lsd1.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Clear conclusions can be drawn for the effects of these changes on IGS cells located anterior to the region 2A-2B border. However, both Gal4 drivers are also expressed in FSCs and their prefollicle cell daughters in addition to IGS cells (Song et al 2004;Decotto and Spradling 2005;Eliazer et al 2014), making it challenging to definitively distinguish labeled posterior IGS cells from FSCs at the region 2A-2B border in order to analyze IGS cell dynamics and identify the mechanisms that control their behavior. Fifteen Gal4 lines that drove expression of UAS-GFP in IGS cells were identified in our screen.…”
Section: ; Morris and Spradling 2011mentioning
confidence: 99%